Creep behaviour of sandstone under different water conditions and its response to varying impact energy - Honglei Liu; Jianhua Zhou; Jinduo Li; Wenxue Deng; Leilei Niu; Tianhong Yang; Shixian Zhang (Geomatics, Natural Hazards & Risk)
Creep deformation and failure of immersed sandstone under mining disturbances are critical factors driving water inrush and goaf collapse. This study employed a specialized creep-impact testing system capable of simultaneous water immersion and mechanical loading, conducting uniaxial compression and creep-impact tests on sandstone samples in three moisture states: dry, saturated, and freshly immersed. The results show that as moisture content increases, both compressive strength and elastic modulus decline significantly. The most notable reductions occurred within the first 2 hours of immersion, with strength and modulus dropping by 55.7% and 70.1%, respectively. Under creep-impact conditions, increasing the impact energy from 14.7 J to 24.5 J caused accelerated creep failure in saturated samples, shortening failure time by 25.2% and increasing the creep rate to 1.32–1.64 times the initial value. In contrast, immersed samples exhibited both accelerated creep and abrupt failure, shortening failure time by 20% but increasing the creep rate more sharply to 2.11–6.04 times the initial value. Post-failure analysis revealed more pronounced fragmentation and a more violent failure process in immersed samples compared to dry or saturated counterparts. These findings offer valuable insights for deep mining operations and the prevention of water inrush disasters.